Can Compression Garments Reduce Inter-Limb Balance Asymmetries? - Noé, Frédéric; Baige, Kévin; Paillard, Thierry (Frontiers in Human Neuroscience, 2022)
Sensory cues provided by compression garments (CG) can improve movement accuracy and potentially reduce inter-limb balance asymmetries and the associated risk of injury. The aim of this study was to analyze the effects of CG wearing on inter-limb balance asymmetries. The hypothesis was that CG would reduce inter-limb balance asymmetries, especially in subjects with high level of asymmetries. Twenty-five sportsmen were recruited. They had to stand as motionless as possible in a one-leg stance in two postural tasks (stable and unstable), while wearing CG or not. Asymmetry indexes were calculated from centre of foot pressure parameters. The effects of CG wearing were analyzed according to participants’ baseline level of asymmetry (i.e., without wearing CG) with correlation analyses. A qualitative analysis was also performed after a dichotomization procedure to check for a specific influence of CG on the dominant and non-dominant leg. Inter-limb balance asymmetries were reduced with CG in participants with high levels of asymmetries at baseline. However, asymmetries were increased with CG in participants with low levels of asymmetries at baseline. The dominant leg was more affected by this negative effect. CG wearing could reduce inter-limb balance asymmetries and the related injury risk in subjects with high levels of inter-limb balance asymmetries at baseline. Nevertheless, CG should not be used in individuals with low baseline balance asymmetries since it can increase asymmetries in these subjects, likely by confusing and overloading the sensorimotor processing on the dominant leg.